IMPROVING THE ELEVENTH GRADE STUDENTS’ READING ABILITY THROUGH THE APPLICATION OF TEAM PAIR SOLO TECHNIQUE AT STATE VOCATIONAL SCHOOL 1 OF LAIS - Arisna Yuliany; Baginda Simaibang; Magdad Hatim (Esteem Journal of English Education Study Programme, 2022)
This research was aimed at improving eleventh grade students’ reading ability by using Team-Pair-Solo Technique when it was applied in teaching reading. The research was carried out through action research. The researcher acted with the students and the English teacher as the collaborator. The subjects of the research were 25 students of Eleventh Grade of State Vocational School of 1 Lais, Musi Banyuasin in the academic year of 2019/2020. Data collection included the application of Team Pair Solo Technique in three cycles. Data were analyzed quantitatively and qualitatively. The research findings showed that Team Pair Solo Technique improve students’ reading comprehension. The technique enabled students to practice some reading strategies in the form of team, pair and individual and it ease them in comprehending reading. The improvement of reading comprehension can be seen from the result of reading test which has the mean score test 1 is 44%, test 2 is 72% and test 3 is 86% This research also showed that the activities in Team-Pair-Solo Technique enhanced students’ ability in comprehending reading. It can be concluded that the application of Team Pair Solo Technique effectively improved the eleventh grade students of State Vocational School 1 of Lais Musi Banyuasin